2021
DOI: 10.3390/app112411803
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Infrared Drying Conditions and Maltodextrin Addition on Some Physicochemical Characteristics of Avocado (Persea americana) Pulp Powder

Abstract: In this study, avocado pulp with a good nutritional profile and economic value was dehydrated using infrared drying to produce pulp powder, which shows potential application in nutritional supplements. An experimental design with two factors, namely maltodextrin level (0% and 9%) and infrared temperature (ranging from 65 to 80 °C), was used. Responses related to the physicochemical properties of the resulted powder were observed, including peroxide value, total polyphenols, total chlorophylls, antioxidant acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…They concluded that the peels and seeds of two avocado varieties, namely, "Hass" and "Fuerte" contain higher amounts of phenolics and antioxidant activity than the avocado pulp, and they have moderate activity against Gram-positive bacteria [28]. In a recent study, the powdered "Maluma" avocado pulp with the highest retention of bioactive compounds and antioxidant activities was successfully produced using the infrared technique [29]. Infrared drying was considered an innovative technique that brings more benefits in the implementation and high retention of dried product quality [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the peels and seeds of two avocado varieties, namely, "Hass" and "Fuerte" contain higher amounts of phenolics and antioxidant activity than the avocado pulp, and they have moderate activity against Gram-positive bacteria [28]. In a recent study, the powdered "Maluma" avocado pulp with the highest retention of bioactive compounds and antioxidant activities was successfully produced using the infrared technique [29]. Infrared drying was considered an innovative technique that brings more benefits in the implementation and high retention of dried product quality [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of maltodextrin was also reported retained food color of the dried product [2], reduce the stickiness of product and improve the flow characteristics of dried powder [3]. Maltodextrin is applied in production of tamarind powder [3], avocado pulp powder [2] and asparagus powder [4]. Those researches reported the beneficial of the application of maltodextrin in fruit and vegetables pulp drying thus the application of maltodextrin in other type of fruit and vegetables pulp drying is need to be studied.…”
Section: Introductionmentioning
confidence: 94%
“…The experimental data was used to validate the thin layer drying kinetics models (Table 1) and the RSS was calculated according to Eq 2. 𝑅𝑆𝑆 = (𝑀𝑅 𝑝𝑟𝑒,𝑖 − 𝑀𝑅 𝑒𝑘𝑠,𝑖 ) 2 [2 Table 1. Drying kinetics models…”
Section: Thin Layer Drying Kineticsmentioning
confidence: 99%
See 2 more Smart Citations